PERIODIC Q-PCR OR CHEST X RAY – WHICH IS MORE IMPORTANT FOR MONITORING POST COVID-19 INFECTION CASE? (CASE REPORT STUDY) - Ravenska Theodora; Hendsun Hendsun; Yohanes Firmansyah; Edwin Destra; Darren Gosal (Yayasan Pendidikan Medika Indonesia, 2021)
Introduction: Coronavirus Disease 2019 (COVID-19) has been an epidemic since December 2019, and has had a huge impact on the world. Various protocols have been established to assess the parameters of post-covid-19 infection, starting from monitoring clinical symptoms and 14-day self-isolation, periodic qPCR examinations, blood laboratories, and radiological examinations. Case Report: A 41-year-old man was diagnosed with SARS-CoV-2 with mild symptoms, on periodic qPCR follow-up examinations, positive qPCR results were obtained even up to the 35th day post-covid-19 infection. Monitoring in terms of clinical symptoms found that all clinical symptoms were in remission on the 5th day after diagnosis. Radiological examination was carried out to assess the patient's improvement on day 36 and the results were bilateral pneumonia in the lungs Discussion: Clinical symptoms and periodic qPCR examinations for monitoring improvement are good to use, but it would be better if radiological examinations were carried out as parameters for improving patients after SARS-CoV-2 infection Conclusion: Radiological examination is an important parameter to assess improvement after SARS-CoV-2 . infection